1863 Idaho Sess. Laws 634 - (:unkn) unknown (My University, 1863)
To Incorporate the City of Idaho in Boise County, § 5: Said mayor and common council shall have full power and authority . . . to regulate the storage of gunpowder and other combustible materials . .
Keywords: GUNPOWDER - STORAGE